Multi-stage cleaning equipment for producing and processing salted duck eggs - ZHA ANCHUN; LIANG YONG; ZHU WANJING; YIN HENGBING; ZHANG WANLIN; CHEN JING (2024)
The invention provides multi-stage cleaning equipment for salted duck egg production and processing, and relates to the technical field of salted duck egg production, the multi-stage cleaning equipment comprises a connecting column, the lower surface of the connecting column is fixedly connected with three connecting rods, the lower surfaces of the connecting rods are fixedly connected with a connecting frame, and the connecting frame is fixedly connected with the connecting column. A bearing plate is fixedly connected to the lower surface of the connecting frame, a lifting air cylinder is started, a first cleaning brush can move downwards, the first cleaning brush is inserted into a small gap between second cleaning brushes, then an operator can pour diluted cleaning liquid into a material conveying pipeline, and due to the gravity, the cleaning liquid can be conveyed into the material conveying pipeline; cleaning liquid reaches a gap in a first cleaning brush, a first driving motor is started, the first dri